آلية التحكيم أمام المركز الدولي لتسوية منازعات الإستثمار - صارة، عيون; قواسمية، أسماء (جامعة باتنة 1 الحاج لخضر - كلية الحقوق والعلوم السياسية, 2022)
للتحكيم دور هام في حسم المنازعات الناشئة عن عقود الاستثمار في إطار المركز الدولي، باعتباره ضمانة إجرائية تسعى إلا تشجيع وحماية الاستثمارات الأجنبية وكذا تحقيق التوافق بين كل من المستثمر الأجنبي -من خلال حماية أمواله المستثمرة والدولة المضيفة التي تسعى دائما لجذب المزيد من الاستثمارات، تطمئن لعدم تدخل دولة المستثمر الأجنبي من خلال وسيلة الحماية الدبلوماسية، فهو من الآليات المناسبة لتسوية منازعات الاستثمار لما يتمتع به من خصائص كالسرعة في الإجراءات السرية، المرونة والفعالية، بداية من اختصاص التحكيم أمام المركز من خلال إتباع مجموعة من الشروط منها ما يتعلق بأطراف النزاع ومنها ما هو مرتبط بموضوعه، مرورا بإجراءات رفع الدعوى وكذا قواعد تشكيل محكمة التحكيم، وصولا إلى صدور الحكم، الذي يتمتع بنوع من الخصوصية من ناحية تنفيذه لأجل ضمان حق المحكوم له من تقاعس الطرف الرافض للتنفيذ. تناولنا من خلال هذه الدراسة مفهوم المركز الدولي، والقواعد المنظمة لسير التحكيم أمام المركز الدولي لتسوية منازعات الاستثمار، بالإضافة إلى خصوصية حكم التحكيم الصادر عن المركز الدولي. Arbitration has an important role to play in resolving disputes arising out of investment contracts within the framework of the International Centre, as a procedural guarantee that seeks to promote and protect foreign investments as well as to achieve compatibility between the foreign investor- by protecting its invested funds- and the host State, which always seeks to attract more investment, reassuring that the State of the foreign investor does not intervene through the means of diplomatic protection, it is an appropriate mechanism for the settlement of investment disputes because of its characteristics such as speed in proceedings, confidentiality, flexibility and Arbitration; International Centre of Investment Disputes Settlement; Washington Convention; Arbitration verdict. effectiveness, beginning with the arbitrate competence before the Centre by following a range of conditions, including those relating to the parties to the dispute and related to its subject matter, through the proceedings and rules of the arbitral tribunal formation down to the verdict; In order to ensure the right of the person that the Judgement passed in his favour, from the inaction of the refusing party of the implementation , it has some form of privacy in its execution. Through this study, we dealt with the concept of the International Cente his tasks, the rules governing the conduct of arbitration before the International Center for Settlement of Investment Disputes, in addition to the specificity of the arbitration ruling issued by the International Center.
Keywords: عقود الاستثمار -- حسم المنازعات -- الضمانات القضائية -- هيئات الاستثمار